THE APPRAISAL SYSTEM OF TOURISM EDITORIAL TEXTS ON SINDONEWS.COM - Aini, Nurul (UIN Raden Mas Said Surakarta, 2024)
This research aimed to identify appraisal system in tourism editorial texts in SINDOnews.com news portal, particularly to identify attitude, graduation, and engagement as well as to know how the writer positions himself in his writing and public response on the issue. This research applied Systemic Functional Linguistics (SFL) theories and is designed with an embedded case study. The data were taken from a tourism editorial text in SINDOnews.com with the total number of 70 out of 30 sentences. The data were then analyzed with appraisal system theory proposed by Martin & White (2005). The result shows the existence of attitude (affect positive/negative), judgement (social esteem positive/negative: normality, capacity, and tenacity; social sanctions positive/negative: veracity and propriety), appreciation (reaction, composition, and valuation positive/negative), graduation (force: Intensifier, attitudinal lexis, metaphor and focus: sharpen and soften) and engagement (monogloss and heterogloss). The data mostly found are graduation which consists of force (8 intensifiers, 6 metaphor, and 2 qttitudinal lexes) and focus (6 sharpen and 8 soften). The texts themselves emphasize values, public opinions, author’s attitude, and show the beautiful and the selling point of tourist destinations in Bali. It means that the writer shows the positive perception subjectively whereas the society shows the positive and negative perception objectively in the texts.